Preventing new sensitization and asthma onset by allergen immunotherapy: the current evidence. Issue 6 (December 2017) - Wahn, Ulrich
Abstract : Purpose of review: Specific allergen immunotherapy is considered a key candidate for a successful preventive intervention in atopic diseases. The strong association of atopic manifestations such as rhinitis and asthma with atopic sensitizations (specific serum IgE) provide a rationale for early intervention in childhood and adolescence. Recent findings: Currently, the documentation of the disease-modifying intervention effects is limited to the secondary prevention of asthma symptoms in children with allergic rhinoconjunctivitis. These effects appear to be rather allergen specific than nonspecific. Summary: Documentation on disease modification including a reduction of asthma symptoms in children, particularly with grass pollen tablets has become quite robust. It is not clear up to now, if the new onset of allergic sensitizations can be modified. So far data on primary prevention are not conclusive.